PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBASIS WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS DI MI MUHAMMADIYAH MALUA - Susan Susanti; Aminullah; Fuad Danindra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model based on Wordwall in improving students’ learning outcomes in science and social studies subjects at MI Muhammadiyah Malua. This research used Classroom Action Research (CAR) with the Kemmis and McTaggart model conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection. The subjects of this study were 12 third-grade students of MI Muhammadiyah Malua. Data collection techniques included tests, observations, interviews, and documentation. The data were analyzed using qualitative and quantitative descriptive analysis. The results showed that the implementation of the Wordwall-based CIRC learning model improved students’ learning outcomes. In the pre-action stage, students’ learning outcomes were still low and most students had not achieved the Minimum Mastery Criteria (KKM). In cycle I, the percentage of students achieving mastery learning reached 67%, while in cycle II it increased to 83%. In addition, students became more active, enthusiastic, and cooperative during the learning process. Therefore, it can be concluded that the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model based on Wordwall is effective in improving students’ learning outcomes in science and social studies subjects.